Hubungan Pacaran Terhadap Perilaku Seks Pranikah Pada Remaja Di Kecamatan Tanjung Sakti Pumi Kabupaten Lahat - Putri, Dia Islami (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
This study aims to determine the relationship of courtship to premarital sexual behavior in adolescents in Tanjung Sakti Pumi District, Lahat Regency. Sources of data in the form of primary data obtained from the scale of premarital sexual behavior and courtship. Based on the Isaac & Micheal table formula with an error rate of 5%, the number of samples in this study was obtained as many as 105 teenagers in Tanjung Sakti Pumi District, Lahat Regency. Data analysis used quantitative analysis using validity test, reliability test, normality test, linearity test and hypothesis testing. Based on the results obtained from the results of data analysis from the discussion, the researchers concluded that there was a courtship relationship with premarital sex behavior in adolescents in Tanjung Sakti Pumi District, Lahat Regency..